Anatomical Study on the Multi-Ovule Development and Abortion of Hanfu Apple - Xu-yuan YANG; Huai-yu MA; Guo-cheng LIU; De-guo LÜ; Si-jun QIN; Guo-dong DU (Journal of Integrative Agriculture, 2014)
The terminal flower buds of 6-yr-old Hanfu apple were used to study the ovule development, ovular characteristics, cell death of abortive ovules, and dynamic change of starch grain quantity in the embryo sac with paraffin slices and terminal deoxynucleotidyl transferase-mediated fluorescein deoxyuridine triphosphate nick-end labeling (TUNEL) system. Four anatropous ovules in each ventricle could be observed before flowering. With the developing of floral organ, the bulk of normal ovules enlarged in each ventricle, the mature embryo sac differentiated into nucellus, and the egg cell developed into zygote by double fertilization. A large number of starch grains were observed during pollen tube growth and double fertilization, which guaranteed basic nutrient supply in the normal development of ovules. Moreover, abortion phenomenon of runtish ovules emerged at the stages of mature embryo sac, double fertilization and zygote development. The abortion characteristics included deformity of ovule development, degradation of nucellus tissue, separation between funiculus and ovule, abnormality of four-nucleate embryo sac, as well as development interruption of mature embryo sac. TUNEL analysis proved that ovule abortion was programmed cell death.